Agroecological transition in a cooperative of family farmers in Itapuranga, Goiás, Brazil - Silva, Fernanda Pereira; Oliveira, Guilherme Resende; Cunha, Cleyzer Adrian; Wander, Alcido Elenor (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
This study aimed to describe the advances, benefits, and difficulties of the agroecological transition of the fruit and vegetable production system in a cooperative of family farmers in Itapuranga, Goias, Brazil, as well as the costs of implementing conventional and agroecological cultivation and the profitability obtained. with agroecological practice. To carry out this research, we used the outline of a described approach that can be classified as exploratory qualitative research that used the case study to carry out the field research. As a data collection instrument, structured questionnaires and unstructured interviews were used. According to the results, the satisfaction of those who work with agroecological practices, those who invested in labor, as well as in technical assistance, is noticeable. Farmers who owned more than 15 hectares of land, agree that their revenues have increased even though they have difficulties to continue the projects due to the lack of technical support after its completion. During execution, technical assistance was identified as a problem due to the high turnover of personnel. Finally, the success of farmers who transitioned from the conventional production system vis-à-vis agroecological resulted, mainly, in greater economic gains, partly from the receipt of inputs and technical assistance from the cooperative. Producers who had more financial resources, qualified labor, social and environmental awareness were those who achieved greater added value to the final product.